Perekrutan dan Radikalisasi Tenaga Kerja Wanita di Hongkong oleh Jaringan Kelompok Islamic State of Iraq and Syria Periode 2014-2016 - Andayani, Agata Eta; Putranti, Ika Riswanti (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2018)
This thesis discuss the phenomenon of Indonesian Female Migrant Worker in Hongkong who recruited and radicalised by ISIS group network in 2014 to 2016. This research aims to analyze why ISIS group network recruit and radicalise Indonesian Female Migrant Worker in Hongkong in 2014 until 2016. This research is an explanative research type that use qualitative method by collecting data from primary and secondary source by doing interview and collecting data from book, journal, report and mass media. The range of this thesis is from 2014 to 2016. This thesis elaborate recruitment and radicalisation concepts, New War Theory and woman and terrorism perspective as the tool of analysis. This thesis resulted in the factors that push ISIS to recruit and radicalise Indonesia Female Migrant Worker from 2014 to 2016. That factors including (i) social and environmental condition of the Indonesian Female Migrant Worker itself, (ii) internet convenience of Indonesia Female Migrant Worker in Hongkong, (iii) economic factor and (iv) gender factor.